PERAN ORANGTUA TERHADAP PENDIDIKAN ANAK DI KUTTAB AL-FATIH PEKANBARU (Kajian Keterlibatan Orangtua dalam Belajar Mandiri) - Nodila, Febria; ", Risdayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Every parents always want their children to be better than them, including on their education. However, most parents rarely get involved with the education they want to give to their children. With the results that appeared some discrepancies between the education their children get at school and at home. Kuttab Al-Fatih is a school for children around 5-12 years old and has a system of parents must be involved in their children’s education.  To support the system, Kuttab Al-Fatih held a Belajar Bersama Orangtua (BBO) program. The research topic is “The Role of Parents for Children’s Education in Kuttab Al-Fatih Pekanbaru (Study of Parent’s Involvement in Self-Study)”. This reseacrh topic is to undestand parents involvement in self-study at house and to understand parents reponse to BBO program at Kuttab Al-Fatih. Research method that used is qulaitative research method. Research location is Kuttab Al-Fatih, SM Amin street, Delima, Tampan, Pekanbaru. There are ten informants on this research, that are 6 informants and 3 key informants which aproppriate to the predetermined criteria (purposive sampling). The technique used is observation, interview and triangulation. Research result generally are most of parents having involvement in self-study in house and getting many benefits in following BBO Kuttab Al-Fatih program.  Keywords : Education, Parents, BBO.